Desarrollo de una aplicación móvil para la gestión y registro de ventas de distribuidores independientes en la ciudad de Villavicencio - Cortés Barrero, David Alberto; Pereira Forero, Jeyson Alejandro (Corporación Universitaria Minuto de Dios, 2021)
El avance de las tencnologias en la actualidad y el impacto que tiene en otros sectores nos impulsó a diseñar como desarrolladores de software una útil herramienta digital con la búsqueda de una problemática que se identificó en nuestro diario vivir, se decide en implementar como proyecto de grado una aplicación móvil que ayude a todos los vendedores independientes, tales como los distribuidores de leche, de agua en botellón, domiciliarios, entre otros. Permitiéndoles llevar en sus dispositivos móviles el manejo de inventario de productos y clientes, además de las cuentas de sus negocios (ventas y gastos), de esta manera optimizar el trabajo de los distribuidores. Además de contar con un sistema GPS en el cual podrá identificar la localización de sus registros de ingresos. Toda esta información estará disponible en la nube, es decir, los datos serán accesibles con conexión a internet y con una cuenta de correo electrónico. En este escrito se podrán encontrar todos los procesos, las consultas e implementaciones que se necesitaron para el desarrollo de esta idea.

The advancement of technology in recent years has been considerable, and it can also be seen that the impact of ICT (Information and Communication Technologies) is not limited only to the sector for which they are produced, but in turn are allowed to adapt to all sectors of production and consumption in society (Merchan et al., 2017). In addition, mobile applications generate innovation by promoting the ease of invention and the production of new services, products or processes in an entrepreneurial environment (Merchan et al., 2017), thus being very helpful for people's work, offering a great variety of solutions and causing most of the population to have a mobile device in their possession, becoming a part of us due to the variety of services they offer us. This prompted us to design as software developers a useful digital tool with the search for a problem that was identified in our daily lives, it was decided to implement as a degree project a mobile application that helps all independent sellers, such as distributors milk, bottled water, domiciliary, among others. Allowing them to carry on their mobile devices the inventory management of products and customers, in addition to their business accounts (sales and expenses), in this way optimizing the work of distributors. In addition to having a GPS system in which you can identify the location of your income records. All this information will be available in the cloud, which means that the data will be accessible on any device that has the application installed and an email account synchronized. In this writing you can find all the processes, queries and implementations that were needed for the development of this idea.
Desarrollar una aplicación móvil que permita la gestión y registro de ventas de distribuidores independientes
Keywords: Aplicación móvil; Distribuidor independiente; GPS; Almacenamiento en la nube; Prototype; Mobile accounting app; Salesperson; Cloud storage